Mortality in Robin sequence: identification of risk factors - Logjes, Robrecht J. H. (Eur J Pediatr, 2018)
Although Robin sequence (RS) is a well-known phenomenon, it is still associated with considerable morbidity and even mortality. The purposes of this study were to gain greater insight into the mortality rate and identify risk factors associated with mortality in RS. We retrospectively reviewed all RS infants followed at the Wilhelmina Children’s Hospital from 1995 to 2016. Outcome measurements were death and causes of death. The authors identified 103 consecutive RS infants with a median follow-up of 8.6 years (range 0.1–21.9 years). Ten of the 103 infants (10%) died at a median age of 0.8 years (range 0.1–5.9 years). Nine of these ten infants (90%) were diagnosed with an associated syndrome. Of these, seven infants died of respiratory insufficiency due to various causes (two related to upper airway obstruction). The other two syndromic RS infants died of arrhythmia due to hypernatremia and of West syndrome with status epilepticus. One isolated RS infant died of brain ischemia after MDO surgery. Cardiac anomalies were observed in 41% and neurological anomalies in 36%. The presence of a neurological anomaly was associated with a mortality rate of 40% versus 7% in infants with no neurological anomaly (p = 0.016), with an odds ratio of 8.3 (95% CI 1.4–49.0) for neurological anomaly versus no neurological anomaly. Mortality was 15% in infants with syndromic RS versus 2% in infants with isolated RS (p = 0.044). Mortality was not significantly associated with the presence of a cardiac anomaly, surgical treatment for severe respiratory distress in the neonatal period, or prematurity. Conclusion: RS represents a heterogeneous patient population and is associated with a high level of underlying syndromes. The present study reports a mortality rate of 10% significantly associated with syndromic RS and the presence of neurological anomalies. A multidisciplinary approach in all infants born with RS, including genetic testing and examination of neurological anomalies in a standardized way, is crucial to identify infants with underlying syndromes potentially associated with increased mortality.